Antimalarial and antimicrobial substances from the endophytic fungus Chaetomium globosum BCC71876 - Nantiya Bunbamrung; Chakapong Intaraudom; Aibrohim Dramae; Nattawut Boonyuen; Wilunda Choowong; Pranee Rachtawee; Chitti Thawai; Pattama Pittayakhajonwut (My University, 2024)
Three previously undescribed compounds including 2',3'-dihydroxy-4,5',4″-trimethoxy-
Keywords: Chaetomium globosum; Chaetomium; Microbial Natural Products and Biosynthesis